8-isoprostane as the main marker of oxidative stress - N. M. Herasymchuk (Zaporožskij Medicinskij Žurnal)
The purpose – is to generalize the data of experimental and clinical studies which have established that the basis of main metabolic processes in humans are redox reactions. Among them, free-radical reactions, leading to the formation of peroxide compounds, play a special role. Thus, it is important to determine the parameters of oxidative stress, its intensity that is necessary for an adequate assessment of the body compensatory capabilities, the prognosis of the disease course and the effectiveness of the treatment received.